Balancing environment, economy and equity: Planning initiatives in three cities in Brazil, Mongolia and India - Ramanathan, Swati; Gandhi, Vidhu (International Planning History Society Proceedings, 2018)
By 2050, 66 per cent of the world’s population will be living in urban areas, with approximately 90 per cent of this increase occurring across Africa and Asia. While urbanisation is proving to be rewarding in terms of providing access to employment and infrastructure, its rapid pace is equally challenging to deal with as poverty, urban sprawl and environmental degradation are some outcomes of urban life that far outweigh the positives. Most often noticeable in developing countries is a trend of disproportionate distribution of population across urban areas, which in most cases has led to huge pressures on land, infrastructure, environment and economy(s) of cities. This paper seeks to examine the role of urban planning and the integration of current concerns of environment, economy and equity into master planning of three cities, on the basis that master plans can be more effective in enabling the sustainable growth of cities. The master plans of three cities – Sawai Madhopur in India, Curitiba in Brazil and Ulaanbaatar in Mongolia, are discussed in this paper with the intention of examining how these cities have dealt with rapid urbanisation and economic growth by employing master planning initiatives that seek to protect the environment, while allowing for sustainable growth in terms of the city’s landuse and its infrastructure.